THE EFFECT OF HERRINGBONE TECHNIQUE ON THE STUDENT’S READING SKILL AT 8TH GRADE JUNIOR HIGH SCHOOL - Wahyu Pambayuningsih (English Education Department, 2018)
This research is purposed to analyze the effect of using herringbone technique on the student’s reading skill. In this research, the researcher used quasi experiment method. There are 2 variables in this research. Herringbone Technique as independent variable (variable x) and Student’s Reading Skill as dependent variable (variable y). The technique of collecting the data by using test, the test consist of 20 items of pre test and 20 items of post test. From the data analyzes, it found that the mean of pre test score is 35,3. The mean of post test score 69,7. The researcher used the pooled variance model t-test to find out the effect variable X towards variable Y. The result of applying pooled variance model t-test, is 2,093 and () is 5,55 the degree of significant 5%. It means is higher than (5,55 > 2,093), so the alternative hypothesis is accepted and null hypothesis is rejected. The conclusion of this research, herringbone technique is effective in teaching reading to improve student’s reading skill.